2023
DOI: 10.1177/24730114231188103
|View full text |Cite
|
Sign up to set email alerts
|

Republication of “Most Readmissions Following Ankle Fracture Surgery Are Unrelated to Surgical Site Issues: An Analysis of 5056 Cases”

Abstract: Background: Ankle fracture surgeries are generally safe and effective procedures; however, as quality-based reimbursement models are increasingly affected by postoperative readmission, we aimed to determine the causes and risk factors for readmission following ankle fracture surgery. Methods: Ankle fracture cases were identified from the prospectively collected American College of Surgeons National Surgical Quality Improvement Program from 2013 to 2014. Demographics, comorbidities, and fracture characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Wound disruption is among the more common reasons for readmission after foot/ankle surgery. 38 Studies have shown that postoperative wound disruption in the foot and ankle is associated with worse morbidity and outcomes in patients with diabetes mellitus. 39 A 2020 CDC report estimated that 16.4% of the American non-Hispanic Black population suffers from diagnosed or undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Wound disruption is among the more common reasons for readmission after foot/ankle surgery. 38 Studies have shown that postoperative wound disruption in the foot and ankle is associated with worse morbidity and outcomes in patients with diabetes mellitus. 39 A 2020 CDC report estimated that 16.4% of the American non-Hispanic Black population suffers from diagnosed or undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%